PENGARUH MANAJEMEN TERKOOPTASI, RASIO PROFITABILITAS DAN ASET TETAP TERHADAP TAX AVOIDANCE - Setiadi Alim Lim (ITB AAS Indonesia, 2026)
Abstract Tax evasion and tax avoidance are common phenomena that occur when taxpayers fulfill their tax obligations to the government, essentially attempting to minimize the amount of tax paid. The difference is that tax evasion is declared illegal, while tax avoidance is categorized as legal. Recently, the term